Pengembangan Bahan Ajar Berorientasi Nature Of Science (NOS) Untuk Meningkatkan Literasi Sains Siswa - Nurlaela, Ela; Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2021)
The background of the research is that based on initial observations at school, it is known that a nature of science oriented module has never been developed due to time constraints due to the many administrative duties of teachers at school. In fact, one way to increase student literacy is based on the nature of science by developing appropriate and good teaching materials. One of the teaching materials developed is in the form of a module. The aim of this research is to determine the implementation and effectiveness of using nature of science oriented modules to increase student literacy. The research method uses a mixed method with an exploratory sequential design. The sample used was taken purposively as many as 60 students of class X Science at SMA Negeri 1 Ciwaru, with 30 students as the control class and 30 students as the experimental class. Data collection techniques include interviews, module validation sheet checklists, scientific literacy tests, questionnaires and documentation. Data analysis used descriptive analysis, mean difference test, and gain index. The results of this research concluded that: (1) The effectiveness of implementing the Nature of Science (NOS) oriented module to increase scientific literacy in environmental pollution material in class tall. (2) Students' scientific literacy skills in environmental pollution material increase through the implementation of the Nature of Science (NOS) oriented module to increase scientific literacy as evidenced by the significant difference in mastery of concepts in the experimental class and the control class with a probability value (p) of 0.000<0.05 , and the experimental class's normalized gain index of 0.35 (medium category) is higher than the control class with a gain index of 0.17 (low category).